If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2z + 4 = 3x + -1 Reorder the terms: 4 + 2z = 3x + -1 Reorder the terms: 4 + 2z = -1 + 3x Solving 4 + 2z = -1 + 3x Solving for variable 'z'. Move all terms containing z to the left, all other terms to the right. Add '-4' to each side of the equation. 4 + -4 + 2z = -1 + -4 + 3x Combine like terms: 4 + -4 = 0 0 + 2z = -1 + -4 + 3x 2z = -1 + -4 + 3x Combine like terms: -1 + -4 = -5 2z = -5 + 3x Divide each side by '2'. z = -2.5 + 1.5x Simplifying z = -2.5 + 1.5x
| 3(-7x+2)=6 | | 39+2v=-3-4(4v-6) | | 8(y-3)+8=4(y+12) | | y=2w^2+w+3 | | -4x-23=37-8x | | 15/8+2+1/4=4 | | 3x-13y=19 | | 33-22q=27-21q+q | | 8x+3=5x-11 | | 8+3b=15 | | -3m=14-4m | | 4a=9+7a | | (-10)x(5)= | | 31+7a=-2(2-6a) | | 4k+7(-4-2k)=-2(-2) | | 4(x^2+3)-5x(x+3)= | | 6+h=7h | | 2x+x-6=2y+4y+2 | | 7x+75=5x-15 | | 9x+2x-12=3x+5-x+6 | | t^2-7t-44=0 | | -5(v+2)+3v+6=5v+6 | | 0.04x+13=0.4x-8.6 | | 4+5t=54 | | 80x^2-24x^3=0 | | 7(w-4)+4=2(w+11) | | 5x-16=x+1 | | 3x-90+x+38= | | 2(1-2z)-3(2z+9)=z-29 | | 3x+9-6+4x=2x-9+4+3+10x | | 72=-8(-4+4r)-2(1+5r) | | 4x^3+16x^2+2x=0 |